Trilineage hematopoietic recovery with romiplostim in a child with down syndrome and aplastic anemia: A case report and review of literature - Dima Abla; Huda Al Habsi; Nasser Al Rahbi; Alyaa Al Mughairy (Elsevier, 2024)
Background: Severe aplastic anemia (SAA) associated with Down syndrome (DS) is a rare hematological disease with only a few cases reported in the literature. The efficacy of standard therapy with either allogeneic hematopoietic stem cell transplantation or immunosuppressive therapy (IST) has not been well studied in patients with DS and AA. Romiplostim, a thrombopoietin receptor agonist, has shown promising results in the treatment of SAA refractory to IST. Case report: We describe a 7-year-old child with DS with severe transfusion-dependent thrombocytopenia. She was diagnosed with SAA based on bone marrow biopsy findings of low cellularity (10 %). As a matched sibling donor was not available, she was started on romiplostim, on which she had a trilineage hematopoietic response. By seven days after the first dose of romiplostim, she became transfusion independent. Conclusion: Our case is the first reported case on the successful treatment of AA with romiplostim in a child with DS. The report supports that romiplostim could be considered for patients lacking a matched sibling donor. Further studies are needed to provide more understanding of long-term remission and the optimal duration of treatment.